Promoting Tourism Marketing and Service Quality in Thailand’s Secondary Tourism Cities - LEE-ANANT, Chayapoj; CHOIBAMROONG, Therdchai; SRIKHWAN, Boonnawat (Journal of Environmental Management and Tourism; Vol 13 No 6 (2022): JEMT, Volume XIII, Issue 6(62), Fall 2022, 2022)
The objective of this paper is to analyse the behaviour of tourists in secondary cities, the expectations of tourism marketing mix and the need for quality’s tourism services in secondary cities. More research actions were conducted to be able to propose guidelines for promoting marketing and service quality in accordance with the behaviour, expectations and the needs of Thai and foreign tourists which prefer these secondary citiesThe quantitative research procedure was preceded by using a questionnaire to gather data from 500 Thai national visitors and 500 foreign visitors. In qualitative research, an in-depth interview was applied to 200 key informants, comprising representatives from the tourism-related private sector, representatives from the government involved in central and local tourism and representatives from tourism communities in secondary cities of Thailand. The results showed that both Thai tourists and foreign tourists had high expectations of the marketing mix and the need for tourism service quality in secondary cities of Thailand both in general and in every particular aspect.